Self-assembled layers for the temporary corrosion protection of magnesium-AZ31 alloy. (June 2020) - K. Korrapati, Vinodh; Scharnagl, Nico; Letzig, Dietmar; Zheludkevich, Mikhail L.
Graphical abstract: Highlights: Retention of the phosphoryl oxygen P=O in XPS, at 533.9 eV BE demonstrates dominant bidentate bonding on Mg-AZ31. Nodule like propagation of phosphates are consistent enough, while the silanes form island/cluster depositions. Cathodic prepolarization testifies that alkalinization can cause an additional conversion of the SA+oxide layers, changing its protective properties by shift in the breakdown potentials. Sealing behavior of the SA-layers are stabilizing the oxide of Mg. The barrier properties are better concluded by considering the Rct and R(oxi + SA) values of EIS. Abstract: Self-assembled (SA) layers of phosphates/silanes/thiols were applied as temporary protective films on Mg-AZ31. Retention of phosphoryl oxygen (PO) on magnesium (Mg), demonstrates dominant bidentate bonding. Distribution of the phosphate nodules are homogeneous, while silanes form island/cluster depositions, apparently sealing the pores and stabilizing the oxide of Mg. Cathodic prepolarization testifies that alkalinization can cause an additional conversion of the SA layers, increasing its protective properties. Although phosphates are with low corrosion rates, hexadecyltrimethoxysilane exhibits high corrosion impedance due to multilayer distribution. The barrier properties are better concluded by considering the resistance (Rct and R(oxi + SA) ) values of impedance measurements.